Annexin A3 in sepsis: novel perspectives from an exploration of public transcriptome data. Issue 4 (31st August 2020) - Toufiq, Mohammed; Roelands, Jessica; Alfaki, Mohamed; Syed Ahamed Kabeer, Basirudeen; Saadaoui, Marwa; Lakshmanan, Arun Prasath; Bangarusamy, Dhinoth Kumar; Murugesan, Selvasankar; Bedognetti, Davide; Hendrickx, Wouter; Al Khodor, Souhaila; Terranegra, Annalisa; et al.
Summary: According to publicly available transcriptome datasets, the abundance of Annexin A3 (ANXA3) is robustly increased during the course of sepsis; however, no studies have examined the biological significance or clinical relevance of ANXA3 in this pathology. Here we explored this interpretation gap and identified possible directions for future research. Based on reference transcriptome datasets, we found that ANXA3 expression is restricted to neutrophils, is upregulated in vitro after exposure to plasma obtained from septic patients, and is associated with adverse clinical outcomes. Secondly, an increase in ANXA3 transcript abundance was also observed in vivo, in the blood of septic patients in multiple independent studies. ANXA3 is known to mediate calcium‐dependent granules–phagosome fusion in support of microbicidal activity in neutrophils. More recent work has also shown that ANXA3 enhances proliferation and survival of tumour cells via a Caspase‐3‐dependent mechanism. And this same molecule is also known to play a critical role in regulation of apoptotic events in neutrophils. Thus, we posit that during sepsis ANXA3 might either play a beneficial role, by facilitating microbial clearance and resolution of the infection; or a detrimental role, by prolonging neutrophil survival, which is known to contribute to sepsis‐mediated organ damage. Abstract : The expression of Annexin A3 (ANXA3), a member of a family of calcium‐binding proteins, is restricted to neutrophils. Its abundance is increased in septic patients, yet the functional relevance of ANXA3 in this context remains unknown. Upon reviewing evidence from public transcriptome repositories and the literature, we hypothesize that during sepsis ANXA3 could mediate neutrophils microbicidal activity while also prolonging their survival, and thus also possibly contributing to organ damage.